Detection of information sources distributing fake information inside global internet network - Soboliev, A. М. (Інститут проблем реєстрації інформації НАН України, 2019)
One of the important segments of the media system in modern conditions is a set of Internet sources. The results of sociological research showed that the number of users on the Internet constantly increases. The most popular network access devices are mobile phones and tablets. This allowed us to expand the range of services are provided through the global network. Information users from the Internet increasingly trust it; first of all, the mass media and social media. This function is also used for manipulative purposes to conduct information wars and attacks to give users fake information. The aim of the media system involves a complex process of bringing information messages in various formats to almost any person without external participation. At the same time, for the functioning of the Internet media, it is usually necessary to create and maintain a site that does not require significant financial costs, as for traditional media. The server can be needed located anywhere in the world, and registration as a mass media requires an application and a small amount of money. Such conditions of creation and functioning give an opportunity to provide an external influence on the mass media system functioning on the Internet. Unstable sources are responsible for the randomness of the dynamic part on the information network and play a key role, reflecting (and to some extent generating) the real patterns of network dynamic. This allows identify the most critical information sources. To determine the stability of an information source is necessary to study the distribution and the number of publications during period of time by determining the coefficient of the normalized division of the amount of published information by the source. In the paper is researcher the stability information sources and is the algorithm developed that allows detecting unstable sources that are used as a tool for information operations to manipulate people's consciousness during the information wars. Tabl.: 2. Fig.: 4. Refs: 14 titles.